2012
DOI: 10.1073/pnas.1206011109
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel measurements of molecular interaction kinetics on a microfluidic platform

Abstract: Quantitative biology requires quantitative data. No high-throughput technologies exist capable of obtaining several hundred independent kinetic binding measurements in a single experiment. We present an integrated microfluidic device (k-MITOMI) for the simultaneous kinetic characterization of 768 biomolecular interactions. We applied k-MITOMI to the kinetic analysis of transcription factor (TF)-DNA interactions, measuring the detailed kinetic landscapes of the mouse TF Zif268, and the yeast TFs Tye7p, Yox1p, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 65 publications
4
98
0
Order By: Relevance
“…Although a potential Hmo1-binding motif (referred to as the IFHL motif) has been described based on motif searches of genome-wide ChIPchip binding data (Hall et al 2006;Lavoie et al 2010), Hmo1 was not thought to recognize this motif directly (Kasahara et al 2007) and was reported to show no binding to multimerized motifs in vivo (Hall et al 2006). However, using oligonucleotide pools constituting a De Bruijn representation of all possible 8-mer DNA sequences in a k-MITOMI (Geertz et al 2012b) analysis of Hmo1 binding, we identified a sequence that is quite similar to the IFHL motif (Supplemental Fig. S2A).…”
Section: Identification Of Two Predominant Promoter Architectures Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a potential Hmo1-binding motif (referred to as the IFHL motif) has been described based on motif searches of genome-wide ChIPchip binding data (Hall et al 2006;Lavoie et al 2010), Hmo1 was not thought to recognize this motif directly (Kasahara et al 2007) and was reported to show no binding to multimerized motifs in vivo (Hall et al 2006). However, using oligonucleotide pools constituting a De Bruijn representation of all possible 8-mer DNA sequences in a k-MITOMI (Geertz et al 2012b) analysis of Hmo1 binding, we identified a sequence that is quite similar to the IFHL motif (Supplemental Fig. S2A).…”
Section: Identification Of Two Predominant Promoter Architectures Atmentioning
confidence: 99%
“…MatrixREDUCE software was used to calculate the position weight matrices (PWMs) for sequences with binding energies >3. The Hmo1 DNA-binding sequence motif was derived using a kinetic MITOMI approach (Geertz et al 2012b). A De Bruijn sequence covering all 8-mer sequence variants was calculated (Philippakis et al 2008) and then synthesized as overlapping oligonucleotide pairs that were converted to dsDNA using Cy3 and Cy5 extension primers (Geertz et al 2012a).…”
Section: Mitomi Measurements and Motif-finding Analysesmentioning
confidence: 99%
“…Geertz et al (28) used mechanically induced trapping of molecular interactions in a microfluidic platform to simultaneously analyze the kinetics of transcription factors binding to their fluorescently labeled DNA ligands-a total of 223 unique interactions. These interactions have a range of K d values and tend to have high association rates and short half-lives, making them challenging to measure using standard techniques (28,29).…”
Section: Characterizing Binding Partners For Affinity-controlled Releasementioning
confidence: 99%
“…26 Recently, the chip design has been improved for fast response times and the chip is now capable of recording association and dissociation traces. 28 In the present publication, we introduce a novel method, which for the first time combines the MFA measurement principle with a microfluidic design. In particular, the button valve of the MITOMI chip is used to apply the force necessary for bond rupture.…”
Section: Microfluidics and Mitomimentioning
confidence: 99%